Pengembangan Perangkat Pembelajaran Ikatan Kimia dengan Model Kooperatif Tipe Jigsaw untuk Meningkatkan Hasil Belajar Peserta Didik SMA - Muttar, Marliana; Danial, Muhammad; Sugiarti, Sugiarti (Program Pasca Sarjana UNM, 2021)
This study is development research (research and development) which aims at examining (1) the development process of chemical bond learning devices using cooperative model of Jigsaw type to improve learning outcomes of senior high school students, (2) the level of validity, practicality, and effectiveness of development product of chemical bond learning devices using cooperative model of Jigsaw type to improve learning outcomes of senior high school students. The development model of learning devices employed in this study was 4.D model which consisted of defining stage, design stage, development stage, and dissemination stage.The learning devices developed in this study were RPP, LKPD, BAPD, media, and THB. The chemical bond learning devices using cooperative model of Jigsaw type was validated by two experts. After being validated, the test of cooperative model of Jigsaw type was conducted at SMAN 7 Jeneponto in class X. MIA 1 with 35 students. The results of the study reveal that the learning devices of cooperative model of Jigsaw type which had been developed indicated that the average validity was 3,75 with very valid criteria. The learning devices of cooperative model of Jigsaw type was stated as practical because the practicality test which related to (1) the implementation of learning devices of cooperative model of Jigsaw type was in average value M = 1.9 in category (1.5 ≤ M ≥ 2.0) which means that the aspect and criteria being observed on the implementation of learning devices of cooperative model of Jigsaw type is in implemented entirely category, (2) the teacher gave very positive response on learning devices of cooperative model of Jigsaw type with 92.07 %, and (3) the students gave very positive response on learning devices based on cooperative model of Jigsaw type with 92.77 %. The learning devices is stated as effective because it has met effective criteria with the learning outcomes obtained the average of 81.91 % and classical completeness 87.50 %, whereas, the improvement of learning outcomes based on N-gain test was 0,78 with high criteria. Therefore, the result of the study indicates that the product of learning devices which had been developed is valid, practical, and effective.